Approaches to the Design and Updating of Educational Programs Competence Models Based on the Intellectual Analysis of Employers’ Vacancies - D. V. Minaev (Управленческое консультирование)
The general logic of the formation of competence models in the interaction of labor market subjects and vocational education institutions is analyzed. Possible gaps in the sequential deployment of competency models along the chain “profession — professional standard — federal state educational standard — educational program” have been identified. The review was carried out taking into account information aspects affecting the possibility of using intelligent machine analysis tools. The key points of the process in which intellectual analysis can play a big role are identified. An example of the practical implementation of such an analysis based on the CNAME analytical platform for a set of 9 heterogeneous master’s programs is presented. The idea of transition to a paradigm of more flexible formation of normative models of competencies is formulated.